2019
DOI: 10.3390/molecules24112130
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils as Antimicrobial Agents—Myth or Real Alternative?

Abstract: Herbs and the essential oils derived from them have been used from the beginning of human history for different purposes. Their beneficial properties have been applied to mask unpleasant odors, attract the attention of other people, add flavor and aroma properties to prepared dishes, perfumes, and cosmetics, etc. Herbs and essential oils (EOs) have also been used in medicine because of their biological properties, such as larvicidal action, analgesic and anti-inflammatory properties, antioxidant, fungicide, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
300
2
19

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(328 citation statements)
references
References 116 publications
7
300
2
19
Order By: Relevance
“…Recently, there has been a growing interest in the use of natural products in medicine. Research has proven that EOs have remarkable antimicrobial potential and are highly effective against bacteria and Candida species [8,15,27]. Several studies have documented that EOs can increase bacterial susceptibility to drugs, even some of the most resistant strains [3,15,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been a growing interest in the use of natural products in medicine. Research has proven that EOs have remarkable antimicrobial potential and are highly effective against bacteria and Candida species [8,15,27]. Several studies have documented that EOs can increase bacterial susceptibility to drugs, even some of the most resistant strains [3,15,28].…”
Section: Discussionmentioning
confidence: 99%
“…During the past several decades, the occurrence of multiresistant bacteria and fungi poses a serious problem worldwide, making choosing the appropriate treatment for patients affected with skin infections a challenge [6,7]. 2 of 15 Natural products, especially essential oils (EOs), have been suggested as antimicrobial agents [8,9]. EOs are known to possess antimicrobial properties against multiresistant bacteria and fungi, due to a broad spectrum of biocidal activity [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in body weight of the test groups of the rats after administration of Chromolaena odorata (linn) fresh leaf extract (Table 4), is justified by Kewuchi et al, 36 who reported a reduction of weight gain produced by the administration of the plant extract. The plant has been reported to be rich in phytochemicals such as flavonoids, terpenes and tannins; and essential oils 16,37,38 . The phytochemical contents of this plant could be responsible for the weight loss in the test animals in this study.…”
Section: Resultsmentioning
confidence: 99%
“…EOs are produced by more than 17,500 species of plants from many angiosperm families, e.g., Lamiaceae, Rutaceae, Myrtaceae, Zingiberaceae and Asteraceae [169]. They are synthesized in the cytoplasm and plastids of plant cells, stored in complex secretory structures like glands or resin conduits, and only then presented as drops in the leaves, stems, flowers, fruits, bark and roots of the plants [170]. EOs are mainly composed of terpenes, terpenoids and phenylpropanoids at the levels of 20%-70% but may also contain fatty acids, oxides and sulfur derivatives [171].…”
Section: Essential Oils (Eos)mentioning
confidence: 99%